Williams–Beuren Syndrome as a Potential Risk Factor for Burkitt Lymphoma - Ryo Kimura; Yuko Ishii; Kiyotaka Tomiwa; Kiyotaka Tomiwa; Kiyotaka Tomiwa; Tomonari Awaya; Tomonari Awaya; Masatoshi Nakata; Takeo Kato; Shin Okazaki; Toshio Heike; Masatoshi Hagiwara (Frontiers in Genetics, 2018)
Williams–Beuren syndrome (WBS) is a multisystemic neurodevelopmental disorder caused by a hemizygous deletion on chromosome 7q11.23. Though at present there is a limited number of reports on WBS patients with tumors, most cases are related to blood cancer in children with WBS. We describe a case of Burkitt lymphoma in a 21-year-old man with WBS. In addition to providing a summary of published reports describing tumors observed in patients with WBS, we present a hypothesis about a possible mechanism of oncogenesis. In particular, we identified some significantly dysregulated cancer-related genes using blood samples from this patient at the age of 19 years (who have not yet developed Burkitt lymphoma). Our findings may provide a new perspective on the relation between WBS and Burkitt lymphoma.